The practices of the leadership LPI and their relationship with the organizational culture faculties deans physical education and sports sciences in Baghdad from the point of view of the members of the teaching staff (Journal of the College of Basic Education, 2022)
The aim of the study to identify the level of the practices of the leadership (LPI) and the level of the organizational culture of the deans of the law faculties of Physical Education and Sport in Baghdad from the point of view of the members of the teaching staff for the period from 2016/3/20 until 2016/4/28 and aggressively pursued researchers descriptive approach in a relational database relations on a sample search of (156) a member of the teaching staff of the research society composed of (311) Member of the teaching staff in the faculties of Physical Education and Sports Sciences at the University of Baghdad and Al-Mostansiriya University، been selected intentional neglect by 50% of the community of origin and variables study and scientific foundations، and thus the application of the exploratory experience the scoping study the president، after dealing with the statistical results pouch system Social Statistical (SPSS) version (V24)، researchers concluded that the deans of the law faculties of Physical Education and Sciences Sport possess the practices of the leadership the LPI from the point of view of the professors due، either the organizational culture was weak level and not at the desired level of the deans of the law faculties of Physical Education and Sports Sciences from the point of view of the professors due and the practices of the leadership LPI linked to organizational culture and the relationship of the moral dots.